COVID‐19 community assessment hubs in Ireland: A study of staff and patient perceptions of their value. (5th November 2022) - McAuliffe, Eilish; Mulcahy Symmons, Sophie; Conlon, Ciara; Rogers, Lisa; De Brún, Aoife; Mannion, Marese; Keane, Niamh; Glynn, Liam; Ryan, Joseph; Quinlan, Diarmuid
Abstract: Background: Critical care bed capacity per capita in Ireland is among the lowest in Europe. The COVID‐19 pandemic has put additional strain on an over‐stretched healthcare system. COVID‐19 community assessment hubs (CAHs) were established to prevent unnecessary admission to acute hospitals and to reduce infection spread. Objective: The aim of this study was to assess the effectiveness and acceptability of CAHs and identify how the service might be improved or adapted for possible future use. Design: This was a mixed methods study, incorporating co‐design with clinical stakeholders. Data collection was via an online survey and semistructured telephone interviews with staff and patients conducted between January and May 2021. Setting and participants: Thirty‐one patients completed the survey and nine were interviewed. Twenty interviews were conducted with staff. Results: The findings suggest that the CAH model was successful in providing a dedicated pathway for assessing patients with COVID‐19 symptoms, whilst mitigating the risk of infection. Patients were particularly positive about the timely, comprehensive and holistic care they received, as well as the accessibility of the clinics and the friendly attitudes of the staff. Staff welcomed the training and clinical protocols which contributed to their feelings of safety and competency in delivering care to this cohort of patients. They also highlighted the benefits of working in a multidisciplinary environment. Both staff and patients felt that the hubs could be repurposed for alternative use, including the treatment of chronic diseases. Discussion: This study describes staff and patients' experiences of these hubs. An unexpected outcome of this study is its demonstration of the true value of effective multidisciplinary working, not only for the staff who were deployed to this service but also for the patients in receipt of care in these hubs. Conclusion: This multidisciplinary patient‐centred service may provide a useful model for the delivery of other services currently delivered in hospital settings. Patient or Public Contribution: An earlier phase of this study involved interviews with COVID‐19‐positive patients on a remote monitoring programme. The data informed this phase. Several of the authors had worked in the CAHs and provided valuable input into the design of the staff and patient interviews.